Management Of Fractured Endodontic Instrument In Root Canal: A Review (International Journal of Food and Nutritional Sciences, 2022)
With advancement in dentistry endodontist has switched to using rotary instrument in recent years, separated rotary nickle-titanium files in the root canals is the most commonly reported mishaps, causing a lot of stress and anxiety among clinicians and patients. No clear guidelines can be drawn from the literature available because there are either too few studies of the effect of the broken files on prognosis, or the few studies that have been performed involved so few patients. The prognosis is also dependent on the file location, prior condition of the pulp, presence or absence of periapical lesion and many other factors. Each case is different. This paper offers a flowchart to help the general dentists and non-endodontist decide which strategy is best when faced with a broken file in the root canal.